INTELLIGENT SYSTEM FOR IDENTIFYING AVOCADO RIPE USING EXTRACTION FEATURES AND K-NEAREST NEIGHBOR METHOD - Maryam Hasan (Jurnal RESTIKOM : Riset Teknik Informatika dan Komputer, 2023)
So far, farmers in harvesting avocados often experience obstacles, namely farmers are still not precise in determining ripe avocados. The ripeness of avocado when harvested is one of the most important factors in maintaining the quality of the avocado. This is due to fatigue and takes a long time so it is not appropriate to determine which avocados are ripe and which are not. Therefore, a system is needed to find out avocados. This study formulates problems in the form of how to identify avocado identification with the KNN method and how to find out how much accuracy the method obtained. While the objectives achieved in this study can identify avocados based on the KNN method and can measure the accuracy of the method with avocado image data. The results obtained in this study were successful in identifying and using the 80% measurement confusion matrix.